Early geological maps of Europe : Central Europe 1750 to 1840 /: Central Europe 1750 to 1840. (2016) - Kozák, Jan, 1938-; Čejchanová, Alena, 1956-; Kukal, Zdeněk; Pošmourný, Karel, 1938-
No abstract available